2003
DOI: 10.1096/fj.02-1147fje
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's disease skin fibroblasts selectively express a bradykinin signaling pathway mediatingtauprotein Ser phosphorylation

Abstract: Increased Ser phosphorylation of tau microtubule-associated protein in the brain is an early feature of Alzheimer's disease (AD) that precedes progression of the disease to frank neuronal disruption. We demonstrate that bradykinin (BK) B2 receptor activation leads to selective Ser phosphorylation of tau in skin fibroblasts from persons who have or will develop AD due to Presenilin 1 mutations or Trisomy 21, but not in skin fibroblasts from normal individuals at any age. The increased signal transduction in AD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 70 publications
1
27
0
Order By: Relevance
“…More recently, however, Zhao et al (2002) reported enhanced and prolonged IP 3 -sensitive Erk1/2 phosphorylation in response to BK stimulation in fibroblasts derived from both familial and sporadic Alzheimer's disease compared with age-matched normal and Huntington's disease controls. Furthermore, B 2 receptor activation was shown to result in selective serine phosphorylation of tau in skin fibroblasts from persons who have or will develop Alzheimer's disease due to presenilin-1 mutations or Trisomy 21, but not in skin fibroblasts from normal individuals at any age (Jong et al, 2003).…”
Section: Neurological Diseasementioning
confidence: 99%
“…More recently, however, Zhao et al (2002) reported enhanced and prolonged IP 3 -sensitive Erk1/2 phosphorylation in response to BK stimulation in fibroblasts derived from both familial and sporadic Alzheimer's disease compared with age-matched normal and Huntington's disease controls. Furthermore, B 2 receptor activation was shown to result in selective serine phosphorylation of tau in skin fibroblasts from persons who have or will develop Alzheimer's disease due to presenilin-1 mutations or Trisomy 21, but not in skin fibroblasts from normal individuals at any age (Jong et al, 2003).…”
Section: Neurological Diseasementioning
confidence: 99%
“…This is not the case in skin fibroblasts from normal individuals at any age. This reflects modification of the G protein-coupled BK B2 receptors themselves suggesting that BK receptor pathway dysfunction may be a molecular signature yielding information about the pathogenesis of AD (Jong et al, 2003).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…A common element of this molecular profile appearing in all presenilin and non-presenilin-based genetic forms of AD risk we tested is the initial BK-induced BKB2R Tyr phosphorylation itself, positioned early in the BKB2R signaling cascade [8], [12], [13], [14]. Beyond this initial step, our present studies now reveal multiple points of divergence in the downstream signaling cascades in AD cells of differing genetic origins.…”
Section: Discussionmentioning
confidence: 55%
“…The PS-2 mutant cells resembled PS-1 mutants in regard to p38 and normal cells in regard to ERK, while Trisomy 21 cells exhibited both BK-dependent p38 activation and ERK activation that was equivalent to normal fibroblasts despite showing other avenues of signal transduction that are like presenilin AD fibroblasts [8]. The functional divergences observed between ERK and p38 may relate to upstream steps in this overall pathway differentially linked to presenilin functions that remain to be defined.…”
Section: Discussionmentioning
confidence: 89%